Walking: mobility that ensures sustainability - Jezeršek, Darka (Journal for Geography, 2011)
The paper deals with the oldest and most basic manner of spatial mobility, walking. Every journey begins and ends with walking. In the past, walking was the main mode of transport, however, with the expansion of motorisation its importance began to decline. Today, it is the most environmentally sustainable form of transport, with zero-emission. The pedestrian impact on the environment is minimal. As a form of physical activity it has a positive effect on people. The first part of the paper offers a theoretical framework of the importance of walking through history, mobility and the concept of sustainability. The analysis of the measures and initiatives taken up in Europe is followed by a review of studies based on the concept of sustainable development and the relationship between urban form and walking. The concept of sustainability has led to the question of how to improve the quality of the urban environment by reducing dependence on cars and introducing non-motorised forms of mobility. The paper concludes with examples of good practice from European cities.
Keywords: walking; concept of sustainability; sustainable mobility; urban form